Incidence of dwarf disease and yield on Inpari 32 over two sequential seasons in Klaten, Central Java - Febrianto, Sudi; Sulandari, Sri; Somowiyarjo, Susamto (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Rice dwarf disease caused by Rice grassy stunt virus (RGSV) and Rice ragged stunt virus (RRSV) is frequently found in Indonesia. This disease is transmitted by brown planthopper/BPH (Nilaparvata lugens Stål). The infected plants become dwarfs and lead to reduced yields. The purpose of this study is to determine the number of BPH populations due to the occurrences of dwarf disease and yield on Inpari 32 rice over two sequential planting seasons in Klaten, Central Java. The observed parameters were dwarf disease symptoms, incidence and intensity of the disease, BPH population and its natural enemy, the vegetative growth, and yields. The analysis used in this study were descriptive analysis and linear regression. The results showed that, plant growth during the dry season was better than the rainy season based on plant height and tiller number. The average population of BPH in the dry season were 0.2–4 individual/hill which is lower than in the rainy season (0.43–4.4 individual/hill). The incidence and intensity of disease in the dry season were lower than rainy season. The higher incidence and intensity of rice dwarf disease in the rainy season caused a decrease in dry harvest yields and milled dry yields were 10.95% and 10.81%, respectively